2015
DOI: 10.1371/journal.pone.0144231
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Kefir-Fermented Milk Consumption on Bone Mineral Density and Bone Metabolism in a Randomized Clinical Trial of Osteoporotic Patients

Abstract: Milk products are good sources of calcium that may reduce bone resorption and help prevent bone loss as well as promote bone remodeling and increase bone formation. Kefir is a product made by kefir grains that degrade milk proteins into various peptides with health-promoting effects, including antithrombotic, antimicrobial and calcium-absorption enhancing bioactivities. In a controlled, parallel, double-blind intervention study over 6 months, we investigated the effects of kefir-fermented milk (1,600 mg) suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 46 publications
3
57
0
11
Order By: Relevance
“…Another study, that saw an effect on bone density, involved the treatment of osteoporotic males (64–67 years of age) with Kefir fermented milk for 6 months. The group found a 5% increase in femoral neck bone mineral density measured by DEXA [67]. This study supports a benefit of probiotics on bone health, but it is important to recognize that only 24 subjects were studied and the contribution of calcium in the Kefir was not separated from the effects of the probiotic bacteria.…”
Section: ) Probiotics and Bone Healthmentioning
confidence: 56%
“…Another study, that saw an effect on bone density, involved the treatment of osteoporotic males (64–67 years of age) with Kefir fermented milk for 6 months. The group found a 5% increase in femoral neck bone mineral density measured by DEXA [67]. This study supports a benefit of probiotics on bone health, but it is important to recognize that only 24 subjects were studied and the contribution of calcium in the Kefir was not separated from the effects of the probiotic bacteria.…”
Section: ) Probiotics and Bone Healthmentioning
confidence: 56%
“…) and short‐term improvements in bone health markers in osteoporosis patients by kefir (Tu et al . ).…”
Section: Fermented Foods: Another Source Of Probiotics?mentioning
confidence: 97%
“…Still, even if fermentation-associated microbes are just passing through, there is emerging evidence that they can nonetheless influence the normal microbiota, communicate with the host immune system and exert other positive effects (reviewed in Marco et al 2017). Outcomes of recent clinical trials include improvements in blood pressure in hypertensive adults by fermented milk (Beltran-Barrientos et al 2018), reduction of infectious disease among children by fermented rice or milk (Nocerino et al 2017) and short-term improvements in bone health markers in osteoporosis patients by kefir (Tu et al 2015).…”
Section: Characteristics Of Probioticsmentioning
confidence: 99%
“…The numbers of participants were similar and were divided randomly into the intervention group and the control group, among which seven studies were designed as double‐blind trials, and three studies were used cross‐control experiments. The studies met the inclusion were performed in six countries, including America (Holloway et al, ), Japan (Takimoto et al, ), Sweden (Nilsson, Sundh, Backhed, & Lorentzon, ), Taiwan (Tu et al, ), India (Gohel et al, ), and Iran (Asemi et al, ; Farhangi et al, ; Jafarnejad et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Two of the four studies reported BMD was included owing to T score report, and the other two studies were excluded from meta‐analysis because of the relative alteration of reported BMD between baseline and end point (Nilsson et al, ; Takimoto et al, ). Finally, six studies were preserved for meta‐analysis (Asemi et al, ; Farhangi et al, ; Gohel et al, ; Holloway et al, ; Jafarnejad et al, ; Tu et al, ). Further details about the included studies were shown in Table S2.…”
Section: Resultsmentioning
confidence: 99%